A fictitious domain approach based on a viscosity penalty method to simulate wave/structure interaction. Issue 6 (2nd November 2017) - Ducassou, B.; Nuñez, J.; Cruchaga, M.; Abadie, S.
ABSTRACT: This work presents an original numerical model for a free surface flow interacting with a spring-block system. The formulation is based on the fictitious domain approach and a penalty method on viscosity to describe the rigid solid motion. The incompressible Navier–Stokes equations are solved in the whole domain and the free surface and the body contour are captured using a volume of fluid method. To describe the rigid body motion, a single degree of freedom model, able to represent translation or rotation, is embedded in the code. The discrete equations are written in a well-known finite volume framework over Cartesian grids. In such a context, the external spring and damping forces are represented as body forces in the solid region. The proposed strategy is tested in a sloshing damping system. The numerical results are compared with experimental data obtained within the present study. Finally, the method is used to simulate a wave energy converter system as an illustration of a rotational case.